(untitled) (Daffodil International University Journal of Science and Technology, 2010)
Secured message transactions are very much desirable for electronic communications in so many ways. A secured message transaction technique has been designed, developed and implemented using Java programming language. For this, a symmetric key encryption technique dynamic Hill cipher has been used for message encryption-decryption with a dynamic key length. A square-matrix of the given key length has been generated with the property that modulo operation of the product of the matrix and the inverse of that matrix is identity. The intended message is converted into binary form. Performs the bitwise-XOR operation of the equal two halves of the binary form and repeats the operations 3 times to generate the message digest (MD), and concatenate it with the message. Encrypts them using the Hill cipher technique with the key matrix and then send them to the destination. In the receiving end, the reverse process is performed to retrieve the message in secured manner. This process can be applied in many cryptographic applications as well as research works. Key Words: Security, Message Security, Message Digest, Hill Cipher and Cipher. DOI: 10.3329/diujst.v5i1.4383 Daffodil International University Journal of Science and Technology Vol.5(1) 2010 pp.62-66